PENERAPAN MODEL CIRC UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD NEGERI NICAH - Abdul Manaf; Nurul Aida Fitri; Cut Nuratifa (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2024)
This study aims to determine how to apply the CIRC model and improve the learning outcomes of 5th grade students at SD Negeri Nicah. The research design used is Classroom Action Research (CAR). The subjects of this study were 5th grade students of SD Negeri Nicah, totaling 34 students consisting of 13 male students and 21 female students. Data collection in the study was carried out by observation, tests, and documentation. The average value of student learning outcomes in cycle I was 59.41 with a percentage of 32.35%. In cycle II, it had started to increase with an average value of 68.52 with a percentage of 58.82%. Furthermore, in cycle III it increased again with an average value of 80.88 with a percentage of 100%.